Understanding Children's Language and Literacy - Mukherji, Penny; O'Dea, Teresa; Hobart, Christine; Frankel, Jill. (Cheltenham : Stanley Thornes, 2000)
This text aims to explain the way in which children's language and literacy develops . It outlines all the key issues in the area and explains sequences of language development and the development of reading, writing, listening and speaking skills.
Includes bibliographical references and index.
Keywords: Preschool children -- Great Britain -- Language; Language acquisition; Reading (Early childhood); Languages